Chemical identification of individual fine dust particles with resonant plasmonic enhancement of nanoslits in the infrared - Vogt, Jochen; Huck, Christian; Tzschoppe, Michael; Neubrech, Frank; Pucci, Annemarie (ACS photonics, 2017)
We demonstrate the capability of single plasmonically active nanoslits for sensing of small fine dust particles via surface-enhanced infrared absorption (SEIRA) spectroscopy. Investigating phononic excitations of individual spherical silica particles coupled to the plasmonic excitation of single nanoslits, we are able to detect and chemically identify single spheres with diameters of 240 nm by their enhanced phononic signal. The single silica spheres in nanoslits lead to Fano-type phononic signals on the plasmonic background. The enhancement of the phononic silica signal is highest for particles located in the middle of the slit, in accordance with the FDTD-simulated near-field distribution along the slit at resonance. Our results reveal, that resonant plasmonic nanoslits are promising substrates for SEIRA spectroscopy of fine and ultra fine dust particles and guide the way toward SEIRA based dust sensing devices.